Exploring fertility preservation in AYA cancer survivors: Information needs and post-cancer challenges - Manon Vialle; Jacqueline Saias-Magnan; Anne Dezamis; Catherine Guillemain; Anne-Déborah Bouhnik; Julien Mancini; Blandine Courbiere (PLoS ONE, 2025)
Purpose To explore the experiences of fertility preservation (FP) and cancer-induced infertility among adolescent and young adult (AYA) cancer survivors. Methods This cross-sectional, qualitative study was conducted by a sociologist in collaboration with a multidisciplinary team specializing in oncology and reproductive medicine. The sample included 31 AYA cancer survivors (13–35 years old) in remission for at least one year. Participants were recruited from oncology or reproductive departments and via “snowball” sampling. Semi-structured interviews, lasting 1–3 hours, were conducted. Results Of the 31 participants (18 women, 13 men), 12 women and 12 men had undergone FP, while 6 women and 1 man had not. Some were fertile, some infertile, and others were unsure of their fertility status. Six women and 5 men had children post-cancer, while others were planning or not considering parenthood. Thus, the respondents’ experiences of fertility were varied, and their analysis led to a number of observations: 1) a lack of attention to infertility risks prior to cancer treatment; 2) fertility preservation not linked to an imminent pregnancy after cancer raises unconsidered difficulties; 3) gaps in information and care beyond the question of fertility. Conclusions The study reveals a lack of information and attention to AYA-specific issues regarding fertility and endocrine function after cancer. There is a need for tailored informational resources for AYA survivors.